Economic Impact Assessment of Brackish Groundwater in Kirana Hills Region, District Chiniot, Pakistan - Rashida Sultana; Maria Salahuddin; Mirza Naseer Ahmad (International Journal of Economic and Environmental Geology, 2018)
Good quality water is the basic need of every citizen. Contaminated water not only affects our health but also damages household items such as sanitary materials. The purpose of this study is to assess the economic impact of high Total Dissolved Solids (TDS) groundwater in Kirana hills region of district Chiniot. In order to evaluate the economic impact in areas of different TDS levels of water, a survey was conducted. The survey form comprised fifteen questions related to health impact, laundry, cooking and sanitary issues. Results of data collected from the respondents of very hard water area indicated that the water causes digestive, skin and hair related diseases. According to the survey, in very hard water areas, washing clothes with groundwater makes them look rough, dull or stained. However, people living in hard water areas responded that the water is relatively better for laundry. Overall residents of very hard water area and hard water area bear costs of rupees 73,850 and 16,200 per five years respectively. By provision of good quality water and taking measures to clean the groundwater, problems can be resolved as the quality of water is positively correlated with the quality of our lives. A collective effort by government and society can minimize the loss by installing appropriate filtration techniques.